Recent Temporal Trend and Variability of Rainfall in Mid-Himalaya Region of Uttarakhand - Kumar, Utkarsh (Indian Forester, 2023)
Agriculture in hill and mountain ecosystem is predominantly rainfed with common occurrence of moisture stress. Due to erratic rainfall and adverse topology in the Indian Himalaya Region (IHR), agricultural drought has become a prime concern. It is a natural disaster which evolves in time and their impacts generally last a long period of time. The present study attempts to characterize annual, seasonal and monthly temporal trend and rainfall pattern of 56 years long-term (1964-2019) and post-urbanization or recent (1971-2019) meteorological data of ICAR-VPKAS, Experimental Farm Hawalbagh observatory located in mid-Himalayan region of Uttarakhand state of India. Man-Kendall (Î± â‰¤ 0.05; Î± â‰¤ 0.10) test, Sen.’s slope and rainfall anomaly index (RAI) were employed for detecting trend, changes in magnitude of rainfall and identifying rainfall deficit year, respectively. Results revealed that RAI analysis frequency of drought year was increasing in last 10 years. The results of study will help in understanding the variation and availability of rainfall in different seasons of the year and motivate to adopt effective water management and agricultural practices for rainfed hills. This study will also be useful for regional, scientific and policy makers for preparing appropriate strategies in order to mitigate adverse impact of climate change in mid-Himalayan region.